2021
DOI: 10.1108/jsm-08-2020-0361
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social media posts on service performance

Abstract: Purpose Much research regarding social media posts and relevancy has resulted in mixed findings. Furthermore, the mediating role of relevancy has not previously been examined. This paper aims to examine the correlating relationship between types of posts made by hotels and the resulting occupancy rates. Then, the mediating role of relevancy is examined and ways that posts can increase/decrease relevancy of the post to potential hotel users. Design/methodology/approach Within the context of the hotel industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Many businesses believe that posting on social media more frequently will improve performance, as social media posting is commonly mentioned in the popular press to directly impact customer intentions (Better Business Bureau, 2019). In contrast, Jones et al (2021) emphasized how performance ultimately depends on the quality of social media posts, not quantity, and argued that posting less frequently might produce more valuable material. In the higher education (HE) setting, Peruta and Shields (2017) found that fewer users interact with each post when universities post more frequently.…”
Section: Introductionmentioning
confidence: 99%
“…Many businesses believe that posting on social media more frequently will improve performance, as social media posting is commonly mentioned in the popular press to directly impact customer intentions (Better Business Bureau, 2019). In contrast, Jones et al (2021) emphasized how performance ultimately depends on the quality of social media posts, not quantity, and argued that posting less frequently might produce more valuable material. In the higher education (HE) setting, Peruta and Shields (2017) found that fewer users interact with each post when universities post more frequently.…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous empirical research on social media has focused on how to adapt a company's marketing mix to this digital environment [4]. In particular, most research analyzes which and how social media content impacts firm performance and customer attitudes and behaviors (e.g., [5]). This is possibly because analyzing the internal management of social media marketing requires access to organizational executives, who are typically harder to reach [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the product era, with the updating and iteration of marketing methods, sensory marketing has emerged from traditional marketing with its new ideas and sensory marketing theory has also become one of the most rapidly developing theories in the field of marketing in recent years. But after reviewing related studies, we found that there are more discussions related to visual marketing in this field, such as color [1][2][3], visual design [4,5], package design [6], the research objects include video [7,8], images [9]. The difference is that auditory marketing research mainly focuses on the speaking style of announcers [10], while auditory marketing communication media similar to destination songs are rarely discussed [11].…”
Section: Introductionmentioning
confidence: 99%